2022
DOI: 10.33088/jmk.v15i2.774
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Faktor Iklim Dan Kepadatan Penduduk Terhadap Kejadian Demam Berdarah Dengue Di Kota Administrasi Jakarta Tahun 2018-2020

Abstract: Problems: Dengue Hemorrhagic Fever (DHF) is a disease that is transmitted through the bite of the Aedes sp. and it is still a public health problem in Indonesia. The survival of the dengue mosquito and the spread of the disease can be affected by climate factors such as rainfall, humidity, and air temperature. Population density is also a risk factor for the spread of dengue fever. The Aim of The Research: The purpose of this study was to determine the relationship between climate factors and population densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…This is in accordance with the statement in the Indonesian Health Profile in 2022 that one of the factors affecting the process of spreading DHF disease is the level of population density. The higher the level of population density, the faster the process of dengue virus transmission by the Aedes aegypti mosquito vector [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the statement in the Indonesian Health Profile in 2022 that one of the factors affecting the process of spreading DHF disease is the level of population density. The higher the level of population density, the faster the process of dengue virus transmission by the Aedes aegypti mosquito vector [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…The Aedes aegypti mosquito is a species that looks for a place to rest in the dark and is protected from the heat of the sun. Sun exposure is one of the key factors that can affect mosquito productivity (Fuadiyah, 2018). Another study by Nia Ratnasari (2014) on climatic factors, larva free rates, and the incidence of dengue fever in Kulon Progo Regency from 2008 to 2013 also showed that the incidence of dengue had a correlation with the length of sunlight.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several similar studies have also been carried out by other researchers in different areas showing that the variable duration of sunlight does not have a significant relationship with dengue cases, for example, the research conducted by Sungono (2004) in 1999-2003in Jakarta and Dini (2009) in 2007-2008 In another study, the duration of sun exposure had a significant correlation with the incidence of dengue hemorrhagic fever. For example, research conducted by Fuadiyah (2018) in Cimahi City, Handayani (2012) in DKI Jakarta, and Silaban (2005) in Bogor.…”
Section: The Relationship Between the Sunshine On The Incidence Of De...mentioning
confidence: 99%
“…Bandung merupakan kota yang penduduknya terhitung padat. Menurut Dimas (2013), kepadatan penduduk memengaruhi kejadian DBD sebesar 16,2% sehingga terdapat faktor lain yang memengaruhi sebesar 83,8%. Kepadatan penduduk dapat memengaruhi jumlah kejadian DBD.…”
unclassified